Parallel Computational Fluid Dynamics 2008 Parallel Numerical Methods, Software Development and Applications - Tromeur-Dervout, Damien; Brenner, Gunther; Emerson, David R.; Erhel, Jocelyne; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book collects the proceedings of the Parallel Computational Fluid Dynamics 2008 conference held in Lyon, France. Contributed papers by over 40 researchers representing the state of the art in parallel CFD and architecture from Asia, Europe, and North America examine major developments in (1) block-structured grid and boundary methods to simulate flows over moving bodies, (2) specific methods for optimization in Aerodynamics Design, (3) innovative parallel algorithms and numerical solvers, such as scalable algebraic multilevel preconditioners and the acceleration of iterative solutions, (4) software frameworks and component architectures for parallelism, (5) large scale computing and parallel efficiencies in the industrial context, (6) lattice Boltzmann and SPH methods, and (7) applications in the environment, biofluids, and nuclear engineering.
Keywords: Physics; Computer-aided engineering; Computer mathematics; Continuum physics; Fluids; Applied mathematics; Engineering mathematics; Physics; Classical Continuum Physics; Appl.Mathematics/Computational Methods of Engineering; Computer-Aided Engineering (CAD, CAE) and Design; Computational Science and Engineering; Fluid- and Aerodynamics; Theoretical, Mathematical and Computational Physics; Electronic books